1998
DOI: 10.1108/eum0000000006796
|View full text |Cite
|
Sign up to set email alerts
|

The role of institutional support in Asian entrepreneurial expansion in Britain

Abstract: This paper examines the role of formal and informal institutional support in the expansion of Asian‐owned businesses in Britain, based on a large survey of Asian entrepreneurs based in Britain. More specifically, it investigates the significance of formal (bank) sources of finance relative to that of informal (family or personal) sources of finance at start‐up and the implications of that reliance on subsequent business expansion. The paper also examines the wider role of informal family and community networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 7 publications
1
51
0
Order By: Relevance
“…However, men were more likely to use family and friends (possibly, as the literature suggests, due to men"s higher level of access to social capital such as business networks Carter and Shaw, 2006;Manolova et al, 2006;Heilbrunn, 2004) (Barrett, 1995;Basu, 1998;Bennett and Robson, 1999a;Ram et al, 2002;Whitehead et al, 2006;Fraser, 2007;Bennett, 2008;Robson et al, 2008). The conclusion here is that Business Link has started to make inroads into the African Caribbean community because of: (a) social capital: there are fewer existing entrepreneurs within African Caribbeans" social networks to give advice; and (b) gender: there may simply be more women entrepreneurs within this community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, men were more likely to use family and friends (possibly, as the literature suggests, due to men"s higher level of access to social capital such as business networks Carter and Shaw, 2006;Manolova et al, 2006;Heilbrunn, 2004) (Barrett, 1995;Basu, 1998;Bennett and Robson, 1999a;Ram et al, 2002;Whitehead et al, 2006;Fraser, 2007;Bennett, 2008;Robson et al, 2008). The conclusion here is that Business Link has started to make inroads into the African Caribbean community because of: (a) social capital: there are fewer existing entrepreneurs within African Caribbeans" social networks to give advice; and (b) gender: there may simply be more women entrepreneurs within this community.…”
Section: Resultsmentioning
confidence: 99%
“…Hussain et al (2008) found that 65 per cent of their sample of BME graduate entrepreneurs -but no African Caribbeans -accessed advice from family and friends. On a cautionary note, Basu (1998) (Fraser, 2007). Although this finding must be treated with caution since it is based on only 8 firms, it suggests prior business experience for Indians (perhaps in family businesses) or high levels of education.…”
Section: Gender Ethnicity Education and Social Capitalmentioning
confidence: 99%
“…As well as operating firms in an intensely competitive milieu (Ram et al, 2000), ethnic minorities may experience problems with access to finance, especially during start-up (Ram and Deakins, 1996;Bank of England, 1999;Ram and Smallbone, 2001;Ram et al, 2003), and particularly African Caribbeans and Bangladeshis, although there may be a strong influence of the business sector in which particular ethnic groups concentrate (Curran and Blackburn, 1993). Ethnic minority owner-managers also favour personal savings and co-ethnic informal sources of finance (Basu, 1998). Smallbone et al (2001) suggested that:…”
Section: Theoretical Background and Conceptual Modelmentioning
confidence: 99%
“…Although a majority of respondents were willing to rely on bank financing at start-up, many were unable to secure loans. This was mainly because of insufficient collateral, but also lack o{ a business plan, unsatisfactory credit terms offered by banks, and other factors (as discussed in Basu, 1999). The human capital resources of the entrepreneurs surveyed are extremely high in contrast with their limited access to financial resources.…”
Section: Resourcesmentioning
confidence: 94%
“…This suggests that they came from a middle-class bourgeois or petit bourgeois background, which is consistent with the findings of earlier studies on the family background of business elites (Fidler, 1981). Four fifths of the entrepreneurs have self-employed relatives in the UK, with some in the same line of business as the respondents themselves (see Basu, 1999, for further details). This implies the existence of social networks in South Asian communities in Britain that can play a useful role in facilitating the exchange of information and advice among community members.…”
Section: Resourcesmentioning
confidence: 99%